Women's Legal Voice: Language, Power, and Gender Performativity in Late Chosŏn Korea. Issue 3 (18th August 2015) - Unknown
Abstract : Based on a neo-Confucian vision that the monarch's mandate relied on listening to his people's grievances, the Chosŏn state (1392–1910) empowered subjects regardless of gender or status to address grievances to the sovereign that had not been rectified in lower courts. Contrary to the preconceived notion that women of the Chosŏn were silent subjects outside their domestic boundary, their petitioning activity shows that women, irrespective of their status, had the same legal capacity as their male counterparts to appeal grievances at local and capital levels. This article focuses on women's petitions and their linguistic practices to show how their petitioning activity complicated the gender dynamics of Confucian society. While the gender hierarchy was reinforced through women's narrative strategy as they appropriated the discourse of domesticity, I posit that women as legal agents were regendering legal identity by constructing a sense of personhood via their petitioning practice. Through articulating their gendered narratives, women struggled to defend not only themselves and their own sense of morality but also their entire family.